New fuzzy preference relations for group decision- making - Tarmudi, Zamali; M., Norfazillah; Md Tap, Abu Osman; Abdullah, Mohd Lazim (American Institute of Physics, 2013)
In this paper, a preference relations based on the conflicting bifuzzy set, namely equilibrium linguistic preference relation was introduced. The concept and some relations were studied briefly which emphasis on the new approach to group decision making process. Then, the negation operator, fuzzy arithmetic averaging operator and balancing coefficient were used to aggregate equilibrium linguistic preference information to the ranking and selection of alternatives. Finally, a numerical example is provided to illustrate the proposed approaches. The results show that the method is highly beneficial and offers a new computation technique for problem solving under fuzzy group decision environment.